The Change in Fingertip Contact Area as a Novel Proprioceptive Cue - A. Moscatelli; M. Bianchi; A. Serio; A. Terekhov; V. Hayward; M. Ernst; A. Bicchi (Current Biology, 2016)
Humans, many animals, and certain robotic hands have deformable fingertip pads. Deformable pads have the advantage of conforming to the objects that are being touched, ensuring a stable grasp for a large range of forces and shapes. Pad deformations change with finger displacements during touch. Pushing a finger against an external surface typically provokes an increase of the gross contact area, potentially providing a relative motion cue, a situation comparable to looming in vision. The rate of increase of the area of contact also depends on the compliance of the object. Because objects normally do not suddenly change compliance, participants may interpret an artificially induced variation in compliance, which coincides with a change in the gross contact area, as a change in finger displacement, and consequently they may misestimate their finger’s position relative to the touched object. To test this, we asked participants to compare the perceived displacements of their finger while contacting an object varying pseudo-randomly in compliance from trial to trial. Results indicate a bias in the perception of finger displacement induced by the change in compliance, hence in contact area, indicating that participants interpreted the altered cutaneous input as a cue to proprioception. This situation highlights the capacity of the brain to take advantage of knowledge of the mechanical properties of the body and of the external environment.
Keywords: Haptics; Robotics

A change in the fingertip contact area induces an illusory displacement of the finger - A. Moscatelli; M. Bianchi; A. Serio; Al Atassi, O.; S. Fani; A. Terekhov; V. Hayward; M. Ernst; A. Bicchi (Eurohaptics, 2014)
Keywords: Haptics; Robotics

Calibration and Test of a Multi-Touch Tactile Object - A. Serio; M Gabiccini; I. Sarakoglou; A. Bicchi (International Conference of Intelligent Robots and Systems - IROS 2012, 2012)
Keywords: Robotics